EVALUATION OF IRRIGATION WATER Quality INDEX (IWQI) FOR MAIN IRAQI RIVERS (TIGRIS, EUPHRATES, ShATT AL-ARAB AND DIYALA) - & Oleiwi, Saloom (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
As a result of different quality standards for irrigation water and the varying ion composition, and the fact that classification of irrigation water consists of large and complex data, this study was conducted in order to find a way for combining the complex water quality data into a single value, a quality of irrigation water index (IWQI) which reflects the suitability of the water quality for irrigation. Irrigation water quality variables were divided into five groups according to Food and Agriculture Organization FAO guide. The order of the parameters were, Salinity expressed in electrical conductivity (EC), Sodium adsorption ratio (SAR), Toxicity of specific ions (boron, chloride, sodium, Toxic trace elements and Miscellaneous effects on sensitive crops (nitrates and bicarbonates and pH). Linear equations of each variable and the formulation of mathematical equations had been done to convert the actual concentration values in the classification adopted to estimate the values of the indicators (sub-indices) and then converting the actual values and different units for each variable to the estimated values under the general scheme consists of grades between (0 -100). For the purpose of calculating irrigation water quality index, a software was originated entitled IWQI program was applied to the data of the irrigation water samples for eighteen (18) locations of water sampling in the rivers: Tigris, Euphrates, Diyala and Shatt al-Arab. Results showed that the values of irrigation water quality index for the period March to December 2015 of the Tigris River were highest than the values of Euphrates River at all locations from the north to the south as it was estimated 94.38 and 88.6 in Muthana bridge site (Tigris) and sader Al- Yusufiya (Euphrates), respectively in Baghdad and reached 74.55 and 67.78 in Qurna (Tigris) and Qurna (Euphrates), respectively. Irrigation water quality index of Shatt al-Arab was at the site of Altnoma 39.78 and classified as almost unsuitable. In Diyala River, it has been observed that the impact of Rustumiya weste water station in reducing the quality of irrigation water quality index was relatively low and water in the two sites (before and after Rustumiya station) are classified as moderately suitable.